Pengaruh Terapi Integrasi Sensori Terhadap Tonus Anak Dengan Sensory Integration Disorder (SID) Berdasarkan Skor Clinical Observation Of Neuromotor Performance (CONP) Di Mitra Ananda Surakarta - Erna Ariyanti Kurnianingsih (Jurnal Keterapian Fisik, 2017)
Abstract: Sensory Integration Therapy-Muscle Tonus-Clinical Observation Of Neuromotor Performance. Special need children such as down syndrome, autism and intellectual disability suffered from Sensory Integration Disorder (SID) will have an impact on the weakness of postural muscle tone. Muscle tone measurement of children with SID is different from other children without SID. Clinical observation of neuromotor performance (CONP) is used as of one of criteria of muscle muscle tone in children with SID. The study aimed at finding theeffect of sensory integration therapy towards muscle tone based on Score of Clinical Observation of Neuromotor Performance (CONP) at Mitra Ananda Surakarta. The study was designed as quasi experiment one group pretest posttest design. population of this study is client with SID at Mitra Ananda Surakarta , by total sampling there are a number of 12 samples. Paired t-test is applied for analizing data with SPSS version 17.0. Paired t-test portrayed p-value > 0.05 it means that there are no significant difference in muscletone, before and after treatment. Sensory integration therapy doesn’t affect muscle tone for shildren with SID Based on Score of Clinical Observation of Neuromotor Performance (CONP) at Mitra Ananda Surakarta